Secondary Hematoma Expansion and Perihemorrhagic Edema after Intracerebral Hemorrhage: From Bench Work to Practical Aspects - Lim-Hing, Krista; Rincon, Fred (Frontiers in Neurology, 2017)
Intracerebral hemorrhages (ICH) represent about 10–15% of all strokes per year in the United States alone. Key variables influencing the long-term outcome after ICH are hematoma size and growth. Although death may occur at the time of the hemorrhage, delayed neurologic deterioration frequently occurs with hematoma growth and neuronal injury of the surrounding tissue. Perihematoma edema has also been implicated as a contributing factor for delayed neurologic deterioration after ICH. Cerebral edema results from both blood–brain barrier disruption and local generation of osmotically active substances. Inflammatory cellular mediators, activation of the complement, by-products of coagulation and hemolysis such as thrombin and fibrin, and hemoglobin enter the brain and induce a local and systemic inflammatory reaction. These complex cascades lead to apoptosis or neuronal injury. By identifying the major modulators of cerebral edema after ICH, a therapeutic target to counter degenerative events may be forthcoming.